Supplementary Table S4 - Litzke, Vivienne; Ottensmann, Meinolf; Forcada, Jaume; Heitzmann, Louise; Hoffman, Joe (Dryad Digital Repository, 2019)
Summary of the 48 neutral loci and the two previously published immune loci (Hoffman and Nichols, 2011) genotyped in this study, including their polymorphism characteristics in 234 Antarctic fur seal individuals.